MYOCARDIAL PERFUSION AND NEUROTROPIC SINGLE-PHOTON EMISSION COMPUTED TOMOGRAPHY FEATURES IN PATIENTS WITH PRIMARY PULMONARY HYPERTENSION - A. A. Ansheles; E. G. Kuznetsova; T. V. Martynyuk; V. B. Sergienko (Вестник рентгенологии и радиологии)
Objective. To compare cardiac 123I-MIBG and 99m Tc-MIBI single-photon emission computed tomography (SPECT) data in patients with primary pulmonary hypertension (PPH).Material and methods. The study included 22 patients with confirmed diagnosis of PPH, with clinical status assessment, Holter ECG monitoring and rest cardiac ultrasound (US) data. All patients, as well as a group of healthy volunteers (n=20) underwent myocardial perfusion SPECT with 99mTc-MIBI at rest and after treadmill exercise test, and myocardial neurotropic SPECT with 123I-MIBG, performed in 15 min (early phase) and 4 hours (delayed phase) after MIBG administration. LV perfusion abnormalities were evaluated using standard SSS and SDS parameters, RV was assessed visually, RV/LV and IVS/LW uptake ratios were calculated. Global sympathetic activity (SA) was assessed with delayed heart/mediastinum ratio (H/Md ) and MIBG Washout Rate in 4 hours (WR). Regional SA abnormalities were assessed using early Summed MIBG Score (SMSe). MIBG RV/LV and LV IVS/LW uptake ratios were calculated. All parameters were compared with normal database (n=20).Results. The values of a number of myocardial SPECT parameters, both perfusion (SSS, RV/LVMIBI, IVS/LWMIBI) and neurotropic (H/Md, WR, SMSe, IVS/LWMIBG), were significantly worse in PPH patients compared to the control group (all p<0.05). Perfusion SPECT showed no significant (SDS>4) transient LV ischemia in all patients, but in 77% of cases IVS perfusion was stably impaired, causing overall SSS=7 (6–10), presumably due to IVS compression by dilated RV. MIBI RV/LV ratio was 0.61±0.02, indicating that RV was clearly visible, with inhomogeneous MIBI uptake in all cases, but without reliable perfusion defects. Values of H/Md were 1.84±0.18, WR: 27±8%, with no reliable correlations with perfusion parameters. Regional SA defects also were located in IVS predominately, causing SMSe mean value of 8 (6–10) and IVS/LW of 0.69±0.09, both parameters correlated with SSS (r=0.44, p=0.04 and r=-0.48, p=0.02, respectively). All parameters, except RV/LVMIBG, had reliable correlations with systolic pulmonary artery pressure assessed by cardiac US, especially RV/LVMIBI(r=0.64, p<0.01), WR (r=0.55, p=0.01) and IVS/LWMIBG(r=-0.49, p=0.02).Conclusion. Combination of myocardial neurotropic and perfusion SPECT has a certain diagnostic value in patients with PPH, since MIBG SPECT reflects SA downregulating, and MIBI SPECT reveals specific microcirculatory abnormalities in these patients, both possibly caused by myocardial pressure overload and responsible for angina-like symptoms.